Preparation and Characterization of Sodium Aluminum Silicate-Polymer Composites and Effects of Surface Roughness and Scratch Directions on Their Flexural Strengths - Cui, Bencang; Sun, Fengbo; Ding, Qian; Wang, Huining; Lin, Yuanhua; Shen, Yang; Li, Ming; Deng, Xuliang; Zhang, Lei; Nan, Cewen (Frontiers in Materials, 2021)
Although efforts have been put into the research in polymer infiltrated ceramic network composites (PICNs), Data are needed to understand the relationship between surface roughness and flexural strength. In this work, a novel dental restorative composite was fabricated via infiltrating mixtures of Bis-GMA/TEGDMA and UDMA/TEGDMA into partially sintered porous sodium aluminum silicate blocks and curing. Bars with different surface conditions were produced by sanding with abrasive and polishing. Flexural strength was measured using three-point-bending. SEM was employed to observe the microstructure of surface areas. 1-way analysis of variance (ANOVA) was applied for statistical calculations with p<0.05 being considered significant. Weibull plots were used to evaluate the reliability of flexural strength. Results demonstrated that the flexural strength of the resultant composites was affected by the scratch direction and the value of roughness. The flexural strength increased with the decreasing of surface roughness. A higher strength value was found for parallel types than for vertical types with nearly the same surface roughness. A large roughness value and a scratch direction perpendicular to tensile stress produced a low weibull modulus. Of particular importance with this work is that these factors should be taken into consideration when using PICNs as dental restorative composites.